Preparation and application of Ag / TiO2 photocatalyst for selective synthesis of benzaldehyde from photocatalytic oxidation of styrene

The photocatalytic oxidation of styrene under normal temperature and pressure by Ag/TiO2 photocatalysts solve the problems of high energy consumption and environmental pollution in traditional synthesis methods, and achieve efficient selective synthesis of benzaldehyde.

CN116474770BActive Publication Date: 2025-04-11INNER MONGOLIA UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310480542.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2025-04-11
Estimated Expiration
2043-04-28

AI Technical Summary

Technical Problem

The prior art has problems in the synthesis of benzaldehyde that have high reaction temperature, large energy consumption, complex routes, environmental pollution, conversion rate and selectivity at the same time.

Method used

The Ag/TiO2 photocatalyst was used to selectively synthesize benzaldehyde by photocatalytic oxidation of styrene. The conditions were at room temperature and pressure. A full-wavelength light source was used for a xenon lamp (300 W) and the reaction time was 1 to 6 hours.

Benefits of technology

The photocatalytic oxidation reaction carried out under normal temperature and pressure is achieved, with mild conditions, low energy consumption, environmentally friendly, and high styrene conversion and benzaldehyde selectivity can be obtained simultaneously.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

Benzaldehyde is the most important aromatic aldehyde in industrial production. Its synthesis process has problems such as high reaction temperature, high energy consumption, complex route, environmental pollution, and inability to obtain both conversion rate and selectivity. The present invention relates to the preparation and application of an Ag / TiO2 photocatalyst for selectively synthesizing benzaldehyde from styrene by photocatalytic oxidation. The catalyst uses AgNO3 as a metal precursor, glucose as a reducing agent, and anatase titanium dioxide as a carrier. The raw materials are cheap and readily available, and the preparation method is simple and easy. It is used in the reaction of selectively synthesizing benzaldehyde from styrene by photocatalytic oxidation, and can simultaneously obtain a high styrene conversion rate and benzaldehyde selectivity. The styrene conversion rate is 77.0%, and the benzaldehyde selectivity is 88.3%. In addition, the reaction process is carried out at normal temperature and pressure, with mild conditions, low energy consumption, and environmental friendliness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation and application of an Ag / TiO2 photocatalyst for selectively synthesizing benzaldehyde by photocatalytic oxidation of styrene. Background Art

[0002] Benzaldehyde is the most important aromatic aldehyde in industrial production and the most basic raw material in benzaldehyde-based fragrances. It has a wide range of uses and is mainly used to synthesize various pharmaceutical products, food additives, plastic additives, and flavors and fragrances. At present, the synthesis of benzaldehyde still has problems such as high reaction temperature, high energy consumption, complex routes, environmental pollution, and inability to achieve both conversion rate and selectivity. For example, CN101456798B discloses a method for preparing benzaldehyde, which uses methyl benzoate, methanol, and water as raw materials, reacts under the conditions of a bifunctional catalyst at a reaction temperature of 300 to 600°C and normal pressure, and the reaction product is post-treated to obtain benzaldehyde; CN109174148B discloses a method for preparing an ultra-thin N-doped nanosheet porous graphite phase carbon nitride supported transition metal oxide catalyst, which is used for catalytic oxidation of toluene to synthesize benzaldehyde, with an oxygen pressure of 1 MPa, a reaction temperature of 160°C, and a reaction time of 12 h. The toluene conversion rate is 10.8%, and the benzaldehyde selectivity is 90.1%.

[0003] Styrene can be synthesized into benzaldehyde through the selective oxidation of the side chain. Traditional thermal catalytic oxidation reactions require high temperature or high pressure conditions, while photocatalytic oxidation reactions are carried out at room temperature and pressure with mild conditions, low energy consumption, and environmental friendliness. Therefore, the selective synthesis of benzaldehyde from styrene by photocatalytic oxidation has potential application prospects. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a Ag / TiO2 photocatalyst and its application in the selective synthesis of benzaldehyde by photocatalytic oxidation of styrene.

[0005] The present invention provides a method for preparing an Ag / TiO2 photocatalyst, and the conditions and steps are as follows: 0.5-2.5 ml of a 5% NH3·H2O solution is added dropwise to 15.9 mL of a 9.225 mmol / L AgNO3 solution, and then 0.3 g of TiO2 (anatase) is added to the mixed solution, and stirred in a water bath at 25°C for 60 min. The water bath temperature is raised to 50-70°C, and then 2.5-7.5 ml of a 5% glucose solution is added dropwise to the system, and stirring is continued for 60 min to obtain a solid-liquid mixture. The solid is washed three times by centrifugal filtration, and then the solid is vacuum dried at 70°C for 10 h, and the obtained dry powder is an Ag / TiO2 photocatalyst with a mass fraction of 5%.

[0006] The invention provides an application of an Ag / TiO2 photocatalyst, which is applied to the selective synthesis of benzaldehyde by photocatalytic oxidation of styrene. The conditions and steps are as follows: 25-75 mg of photocatalyst, 0.5 ml of styrene, 2.5-7.5 ml of acetonitrile and 1.5-4.5 ml of 70 wt.% tert-butyl hydroperoxide aqueous solution are accurately added into a photocatalytic reaction kettle, the reaction kettle is sealed, the wavelength of a xenon lamp (300 W) is adjusted to a full wavelength, the reaction is stirred for 1-6 hours, and after the reaction is completed, the catalyst solid and liquid are separated by centrifugation, the filtrate is analyzed by gas chromatography, and the conversion rate of styrene and the selectivity of benzaldehyde are calculated.

[0007] The beneficial effects of the present invention are as follows: the raw materials of Ag / TiO2 photocatalyst are cheap and easy to obtain, the preparation method is simple, and the utilization efficiency is high. Ag / TiO2 photocatalyst is used in the photocatalytic oxidation of styrene to selectively synthesize benzaldehyde, at room temperature and pressure, with mild reaction conditions, low energy consumption, and environmental friendliness, and can simultaneously obtain a high styrene conversion rate and benzaldehyde selectivity.

[0008] Example 1: 0.5 ml of 5% NH3·H2O solution was added dropwise to 15.9 mL of 9.225 mmol / L AgNO3 solution, and then 0.3 g of TiO2 (anatase) was added to the mixed solution, and stirred in a water bath at 25°C for 60 min. The water bath temperature was raised to 60°C, and 5.0 ml of 5% glucose solution was added dropwise to the above system, and stirring was continued for 60 min to obtain a solid-liquid mixture. The solid was washed three times by centrifugal filtration, and then the solid was vacuum dried at 70°C for 10 h. The obtained dry powder was a 5% Ag / TiO2 photocatalyst by mass. Accurately add 50 mg of photocatalyst, 0.5 ml of styrene, 5.0 ml of acetonitrile and 3.0 ml of 70 wt.% tert-butyl hydroperoxide aqueous solution into the photocatalytic reactor, seal the reactor, adjust the wavelength of the xenon lamp (300W) to full wavelength, stir and react for 3 h. After the reaction, centrifuge to separate the catalyst solid and liquid, and perform gas chromatography analysis on the filtrate. The conversion rate of styrene is 8.1%, and the selectivity of benzaldehyde is 94.6%.

[0009] Example 2: 1.5 ml of 5% NH3·H2O solution was added dropwise to 15.9 mL of 9.225 mmol / L AgNO3 solution, and then 0.3 g of TiO2 (anatase) was added to the mixed solution, and stirred in a water bath at 25°C for 60 min. The water bath temperature was raised to 60°C, and 5.0 ml of 5% glucose solution was added dropwise to the above system, and stirring was continued for 60 min to obtain a solid-liquid mixture. The solid was washed three times by centrifugal filtration, and then the solid was vacuum dried at 70°C for 10 h. The obtained dry powder was a 5% Ag / TiO2 photocatalyst by mass. 50 mg of photocatalyst, 0.5 ml of styrene, 5.0 ml of acetonitrile and 3.0 ml of 70 wt.% tert-butyl hydroperoxide aqueous solution were accurately added into the photocatalytic reactor, the reactor was sealed, the wavelength of the xenon lamp (300 W) was adjusted to full wavelength, and the reaction was stirred for 3 h. After the reaction, the catalyst solid and liquid were separated by centrifugation, and the filtrate was analyzed by gas chromatography. The conversion rate of styrene was 48.6%, and the selectivity of benzaldehyde was 86.3%.

[0010] Example 3: 2.5 ml of 5% NH3·H2O solution was added dropwise to 15.9 mL of 9.225 mmol / L AgNO3 solution, and then 0.3 g of TiO2 (anatase) was added to the mixed solution, and stirred in a water bath at 25°C for 60 min. The water bath temperature was raised to 60°C, and 5.0 ml of 5% glucose solution was added dropwise to the above system, and stirring was continued for 60 min to obtain a solid-liquid mixture. The solid was washed three times by centrifugal filtration, and then the solid was vacuum dried at 70°C for 10 h. The obtained dry powder was a 5% Ag / TiO2 photocatalyst by mass. Accurately add 50 mg of photocatalyst, 0.5 ml of styrene, 5.0 ml of acetonitrile and 3.0 ml of 70 wt.% tert-butyl hydroperoxide aqueous solution into the photocatalytic reactor, seal the reactor, adjust the wavelength of the xenon lamp (300W) to full wavelength, stir and react for 3 h. After the reaction, centrifuge to separate the catalyst solid and liquid, and perform gas chromatography analysis on the filtrate. The conversion rate of styrene is 2.6%, and the selectivity of benzaldehyde is 84.9%.

[0011] Example 4: 1.5 ml of 5% NH3·H2O solution was added dropwise to 15.9 mL of 9.225 mmol / L AgNO3 solution, and then 0.3 g of TiO2 (anatase) was added to the mixed solution, and stirred in a water bath at 25°C for 60 min. The water bath temperature was raised to 50°C, and 5.0 ml of 5% glucose solution was added dropwise to the above system, and stirring was continued for 60 min to obtain a solid-liquid mixture. The solid was washed three times by centrifugal filtration, and then the solid was vacuum dried at 70°C for 10 h. The obtained dry powder was a 5% Ag / TiO2 photocatalyst by mass. Accurately add 50 mg of photocatalyst, 0.5 ml of styrene, 5.0 ml of acetonitrile and 3.0 ml of 70 wt.% tert-butyl hydroperoxide aqueous solution into the photocatalytic reactor, seal the reactor, adjust the wavelength of the xenon lamp (300W) to full wavelength, stir and react for 3 h. After the reaction, centrifuge to separate the catalyst solid and liquid, and perform gas chromatography analysis on the filtrate. The conversion rate of styrene is 7.0%, and the selectivity of benzaldehyde is 95%.

[0012] Example 5: 1.5 ml of 5% NH3·H2O solution was added dropwise to 15.9 mL of 9.225 mmol / L AgNO3 solution, and then 0.3 g of TiO2 (anatase) was added to the mixed solution, and stirred in a water bath at 25°C for 60 min. The water bath temperature was raised to 70°C, and 5.0 ml of 5% glucose solution was added dropwise to the above system, and stirring was continued for 60 min to obtain a solid-liquid mixture. The solid was washed three times by centrifugal filtration, and then the solid was vacuum dried at 70°C for 10 h. The obtained dry powder was a 5% Ag / TiO2 photocatalyst by mass. Accurately add 50 mg of photocatalyst, 0.5 ml of styrene, 5.0 ml of acetonitrile and 3.0 ml of 70 wt.% tert-butyl hydroperoxide aqueous solution into the photocatalytic reactor, seal the reactor, adjust the wavelength of the xenon lamp (300W) to full wavelength, stir and react for 3 h. After the reaction, centrifuge to separate the catalyst solid and liquid, and perform gas chromatography analysis on the filtrate. The conversion rate of styrene is 20%, and the selectivity of benzaldehyde is 95.5%.

[0013] Example 6: 1.5 ml of 5% NH3·H2O solution was added dropwise to 15.9 mL of 9.225 mmol / L AgNO3 solution, and then 0.3 g of TiO2 (anatase) was added to the mixed solution, and stirred in a water bath at 25°C for 60 min. The water bath temperature was raised to 60°C, and 2.5 ml of 5% glucose solution was added dropwise to the above system, and stirring was continued for 60 min to obtain a solid-liquid mixture. The solid was washed three times by centrifugal filtration, and then the solid was vacuum dried at 70°C for 10 h. The obtained dry powder was a 5% Ag / TiO2 photocatalyst by mass. Into the photocatalytic reactor, 50 mg of photocatalyst, 0.5 ml of styrene, 5.0 ml of acetonitrile and 3.0 ml of 70 wt.% tert-butyl hydroperoxide aqueous solution were accurately added, the reactor was sealed, the wavelength of the xenon lamp (300 W) was adjusted to full wavelength, and the reaction was stirred for 3 h. After the reaction, the catalyst solid and liquid were separated by centrifugation, and the filtrate was analyzed by gas chromatography. The conversion rate of styrene was 2.0%, and the selectivity of benzaldehyde was 96.3%.

[0014] Example 7: 1.5 ml of 5% NH3·H2O solution was added dropwise to 15.9 mL of 9.225 mmol / L AgNO3 solution, and then 0.3 g of TiO2 (anatase) was added to the mixed solution, and stirred in a water bath at 25°C for 60 min. The water bath temperature was raised to 60°C, and 7.5 ml of 5% glucose solution was added dropwise to the above system, and stirring was continued for 60 min to obtain a solid-liquid mixture. The solid was washed three times by centrifugal filtration, and then the solid was vacuum dried at 70°C for 10 h. The obtained dry powder was a 5% Ag / TiO2 photocatalyst by mass. Into the photocatalytic reactor, 50 mg of photocatalyst, 0.5 ml of styrene, 5.0 ml of acetonitrile and 3.0 ml of 70 wt.% tert-butyl hydroperoxide aqueous solution were accurately added, the reactor was sealed, the wavelength of the xenon lamp (300 W) was adjusted to full wavelength, and the reaction was stirred for 3 h. After the reaction, the catalyst solid and liquid were separated by centrifugation, and the filtrate was analyzed by gas chromatography. The conversion rate of styrene was 20.6%, and the selectivity of benzaldehyde was 97.9%.

[0015] Example 8: 1.5 ml of 5% NH3·H2O solution was added dropwise to 15.9 mL of 9.225 mmol / L AgNO3 solution, and then 0.3 g of TiO2 (anatase) was added to the mixed solution, and stirred in a water bath at 25°C for 60 min. The water bath temperature was raised to 60°C, and 5.0 ml of 5% glucose solution was added dropwise to the above system, and stirring was continued for 60 min to obtain a solid-liquid mixture. The solid was washed three times by centrifugal filtration, and then the solid was vacuum dried at 70°C for 10 h. The obtained dry powder was a 5% Ag / TiO2 photocatalyst by mass. 25 mg of photocatalyst, 0.5 ml of styrene, 5.0 ml of acetonitrile and 3.0 ml of 70 wt.% tert-butyl hydroperoxide aqueous solution were accurately added into the photocatalytic reactor, the reactor was sealed, the wavelength of the xenon lamp (300W) was adjusted to full wavelength, and the reaction was stirred for 6 h. After the reaction, the catalyst solid and liquid were separated by centrifugation, and the filtrate was analyzed by gas chromatography. The conversion rate of styrene was 56.5%, and the selectivity of benzaldehyde was 92.1%.

[0016] Example 9: 1.5 ml of 5% NH3·H2O solution was added dropwise to 15.9 mL of 9.225 mmol / L AgNO3 solution, and then 0.3 g of TiO2 (anatase) was added to the mixed solution, and stirred in a water bath at 25°C for 60 min. The water bath temperature was raised to 60°C, and 5.0 ml of 5% glucose solution was added dropwise to the above system, and stirring was continued for 60 min to obtain a solid-liquid mixture. The solid was washed three times by centrifugal filtration, and then the solid was vacuum dried at 70°C for 10 h. The obtained dry powder was a 5% Ag / TiO2 photocatalyst by mass. Into the photocatalytic reactor, 50 mg of photocatalyst, 0.5 ml of styrene, 5.0 ml of acetonitrile and 3.0 ml of 70 wt.% tert-butyl hydroperoxide aqueous solution were accurately added, the reactor was sealed, the wavelength of the xenon lamp (300 W) was adjusted to full wavelength, and the reaction was stirred for 6 h. After the reaction, the catalyst solid and liquid were separated by centrifugation, and the filtrate was analyzed by gas chromatography. The conversion rate of styrene was 77.0%, and the selectivity of benzaldehyde was 88.3%.

[0017] Example 10: 1.5 ml of 5% NH3·H2O solution was added dropwise to 15.9 mL of 9.225 mmol / L AgNO3 solution, and then 0.3 g of TiO2 (anatase) was added to the mixed solution, and stirred in a water bath at 25°C for 60 min. The water bath temperature was raised to 60°C, and 5.0 ml of 5% glucose solution was added dropwise to the above system, and stirring was continued for 60 min to obtain a solid-liquid mixture. The solid was washed three times by centrifugal filtration, and then the solid was vacuum dried at 70°C for 10 h. The obtained dry powder was a 5% Ag / TiO2 photocatalyst by mass. 75 mg of photocatalyst, 0.5 ml of styrene, 5.0 ml of acetonitrile and 3.0 ml of 70 wt.% tert-butyl hydroperoxide aqueous solution were accurately added into the photocatalytic reactor, the reactor was sealed, the wavelength of the xenon lamp (300 W) was adjusted to full wavelength, and the reaction was stirred for 6 h. After the reaction, the catalyst solid and liquid were separated by centrifugation, and the filtrate was analyzed by gas chromatography. The conversion rate of styrene was 75.2%, and the selectivity of benzaldehyde was 84.7%.

[0018] Example 11: 1.5 ml of 5% NH3·H2O solution was added dropwise to 15.9 mL of 9.225 mmol / L AgNO3 solution, and then 0.3 g of TiO2 (anatase) was added to the mixed solution, and stirred in a water bath at 25°C for 60 min. The water bath temperature was raised to 60°C, and 5.0 ml of 5% glucose solution was added dropwise to the above system, and stirring was continued for 60 min to obtain a solid-liquid mixture. The solid was washed three times by centrifugal filtration, and then the solid was vacuum dried at 70°C for 10 h. The obtained dry powder was a 5% Ag / TiO2 photocatalyst by mass. In the photocatalytic reactor, 50 mg of photocatalyst, 0.5 ml of styrene, 2.5 ml of acetonitrile and 3.0 ml of 70 wt.% tert-butyl hydroperoxide aqueous solution were accurately added respectively, the reactor was sealed, the wavelength of the xenon lamp (300W) was adjusted to full wavelength, and the reaction was stirred for 6 h. After the reaction, the catalyst solid and liquid were separated by centrifugation, and the filtrate was analyzed by gas chromatography. The conversion rate of styrene was 62.3%, and the selectivity of benzaldehyde was 86.8%.

[0019] Example 12: 1.5 ml of 5% NH3·H2O solution was added dropwise to 15.9 mL of 9.225 mmol / L AgNO3 solution, and then 0.3 g of TiO2 (anatase) was added to the mixed solution, and stirred in a water bath at 25°C for 60 min. The water bath temperature was raised to 60°C, and 5.0 ml of 5% glucose solution was added dropwise to the above system, and stirring was continued for 60 min to obtain a solid-liquid mixture. The solid was washed three times by centrifugal filtration, and then the solid was vacuum dried at 70°C for 10 h. The obtained dry powder was a 5% Ag / TiO2 photocatalyst by mass. Into the photocatalytic reactor, 50 mg of photocatalyst, 0.5 ml of styrene, 7.5 ml of acetonitrile and 3.0 ml of 70 wt.% tert-butyl hydroperoxide aqueous solution were accurately added, the reactor was sealed, the wavelength of the xenon lamp (300 W) was adjusted to full wavelength, and the reaction was stirred for 6 h. After the reaction, the catalyst solid and liquid were separated by centrifugation, and the filtrate was analyzed by gas chromatography. The conversion rate of styrene was 54.6%, and the selectivity of benzaldehyde was 83.1%.

[0020] Example 13: 1.5 ml of 5% NH3·H2O solution was added dropwise to 15.9 mL of 9.225 mmol / L AgNO3 solution, and then 0.3 g of TiO2 (anatase) was added to the mixed solution, and stirred in a water bath at 25°C for 60 min. The water bath temperature was raised to 60°C, and 5.0 ml of 5% glucose solution was added dropwise to the above system, and stirring was continued for 60 min to obtain a solid-liquid mixture. The solid was washed three times by centrifugal filtration, and then the solid was vacuum dried at 70°C for 10 h. The obtained dry powder was a 5% Ag / TiO2 photocatalyst by mass. Into the photocatalytic reactor, 50 mg of photocatalyst, 0.5 ml of styrene, 5.0 ml of acetonitrile and 1.5 ml of 70 wt.% tert-butyl hydroperoxide aqueous solution were accurately added, the reactor was sealed, the wavelength of the xenon lamp (300 W) was adjusted to full wavelength, and the reaction was stirred for 6 h. After the reaction, the catalyst solid and liquid were separated by centrifugation, and the filtrate was analyzed by gas chromatography. The conversion rate of styrene was 39.1%, and the selectivity of benzaldehyde was 90.9%.

[0021] Example 14: 1.5 ml of 5% NH3·H2O solution was added dropwise to 15.9 mL of 9.225 mmol / L AgNO3 solution, and then 0.3 g of TiO2 (anatase) was added to the mixed solution, and stirred in a water bath at 25°C for 60 min. The water bath temperature was raised to 60°C, and 5.0 ml of 5% glucose solution was added dropwise to the above system, and stirring was continued for 60 min to obtain a solid-liquid mixture. The solid was washed three times by centrifugal filtration, and then the solid was vacuum dried at 70°C for 10 h. The obtained dry powder was a 5% Ag / TiO2 photocatalyst by mass. 50 mg of photocatalyst, 0.5 ml of styrene, 5.0 ml of acetonitrile and 4.5 ml of 70 wt.% tert-butyl hydroperoxide aqueous solution were accurately added into the photocatalytic reactor, the reactor was sealed, the wavelength of the xenon lamp (300 W) was adjusted to full wavelength, and the reaction was stirred for 6 h. After the reaction, the catalyst solid and liquid were separated by centrifugation, and the filtrate was analyzed by gas chromatography. The conversion rate of styrene was 66.1%, and the selectivity of benzaldehyde was 84.7%.

[0022] Example 15: 1.5 ml of 5% NH3·H2O solution was added dropwise to 15.9 mL of 9.225 mmol / L AgNO3 solution, and then 0.3 g of TiO2 (anatase) was added to the mixed solution, and stirred in a water bath at 25°C for 60 min. The water bath temperature was raised to 60°C, and 5.0 ml of 5% glucose solution was added dropwise to the above system, and stirring was continued for 60 min to obtain a solid-liquid mixture. The solid was washed three times by centrifugal filtration, and then the solid was vacuum dried at 70°C for 10 h. The obtained dry powder was a 5% Ag / TiO2 photocatalyst by mass. Accurately add 50 mg of photocatalyst, 0.5 ml of styrene, 5.0 ml of acetonitrile and 3.0 ml of 70 wt.% tert-butyl hydroperoxide aqueous solution into the photocatalytic reactor, seal the reactor, adjust the wavelength of the xenon lamp (300W) to full wavelength, stir and react for 1 h. After the reaction, centrifuge to separate the catalyst solid and liquid, and perform gas chromatography analysis on the filtrate. The conversion rate of styrene is 6.3%, and the selectivity of benzaldehyde is 99.9%.

[0023] Example 16: 1.5 ml of 5% NH3·H2O solution was added dropwise to 15.9 mL of 9.225 mmol / L AgNO3 solution, and then 0.3 g of TiO2 (anatase) was added to the mixed solution, and stirred in a water bath at 25°C for 60 min. The water bath temperature was raised to 60°C, and 5.0 ml of 5% glucose solution was added dropwise to the above system, and stirring was continued for 60 min to obtain a solid-liquid mixture. The solid was washed three times by centrifugal filtration, and then the solid was vacuum dried at 70°C for 10 h. The obtained dry powder was a 5% Ag / TiO2 photocatalyst by mass. 50 mg of photocatalyst, 0.5 ml of styrene, 5.0 ml of acetonitrile and 3.0 ml of 70 wt.% tert-butyl hydroperoxide aqueous solution were accurately added into the photocatalytic reactor, the reactor was sealed, the wavelength of the xenon lamp (300 W) was adjusted to full wavelength, and the reaction was stirred for 5 h. After the reaction, the catalyst solid and liquid were separated by centrifugation, and the filtrate was analyzed by gas chromatography. The conversion rate of styrene was 56.0%, and the selectivity of benzaldehyde was 92.3%.

[0024] Example 17: 0.5 ml of styrene, 5.0 ml of acetonitrile and 3.0 ml of 70 wt.% tert-butyl hydroperoxide aqueous solution were accurately added to a photocatalytic reactor, the reactor was sealed, the wavelength of a xenon lamp (300 W) was adjusted to full wavelength, and the reaction was stirred for 3 h. After the reaction was completed, the catalyst solid and liquid were separated by centrifugation, and the filtrate was analyzed by gas chromatography. The conversion rate of styrene was 20.9%, and the selectivity of benzaldehyde was 53.1%.

[0025] Example 18: 50 mg TiO2 (anatase), 0.5 ml styrene, 5.0 ml acetonitrile and 3.0 ml 70 wt.% tert-butyl hydroperoxide aqueous solution were accurately added into a photocatalytic reactor, the reactor was sealed, the wavelength of the xenon lamp (300 W) was adjusted to full wavelength, and the reaction was stirred for 3 h. After the reaction was completed, the catalyst solid and liquid were separated by centrifugation, and the filtrate was analyzed by gas chromatography. The conversion rate of styrene was 33.4%, and the selectivity of benzaldehyde was 84.0%.

Claims

1. An application of Ag / TiO2 photocatalyst for selective synthesis of benzaldehyde by photocatalytic oxidation of styrene, characterized in that: 50 mg Ag / TiO2 photocatalyst, 0.5 ml styrene, 5.0 ml acetonitrile and 3.0 ml 70 wt.% tert-butyl hydroperoxide aqueous solution were accurately added into a photocatalytic reaction kettle, the reaction kettle was sealed, irradiated with a xenon lamp light source, stirred for 6 hours, and after the reaction, the catalyst solid and liquid were separated by centrifugation, and the liquid was analyzed by gas chromatography. Under the conditions that the parameters of the xenon lamp light source were 300 W of power and the illumination wavelength was full wavelength, the conversion rate of styrene was 77.0%, and the selectivity of benzaldehyde was 88.3%; the preparation method of the Ag / TiO2 photocatalyst was as follows: 1.5 ml 5 wt.% NH3·H2O solution was dropwise added into 15.9 mL 9.225 mmol / L AgNO3 solution, and then 0.3 g rutile TiO2 was added into the mixed solution, stirred in a 25°C water bath for 60 minutes, the water bath temperature was raised to 60°C, and 5.0 ml 5wt.% glucose solution, continue stirring for 60min to obtain a solid-liquid mixture, wash the solid three times by centrifugal filtration, and then vacuum dry the solid at 70°C for 10h. The obtained dry powder is a 5wt.% Ag / TiO2 photocatalyst.

Citation Information

Patent Citations

  • Process for synthesizing benzaldehyde

    CN101456798B

  • A catalyst for the catalytic oxidation of toluene to benzaldehyde and its preparation method

    CN109174148B

  • Preparation of gold-silver alloy catalyst and method for gas-phase photocatalysis of ethyl alcohol to synthesize ethylene, acetaldehyde and acetone employing gold-silver alloy catalyst

    CN106883088A

  • Preparation of loaded type Ag catalyst and technology for performing gas-phase photocatalytic partial oxidization to ethanol to synthesize ethylene, acetaldehyde and acetone

    CN106883107A